Bayes and Laplace Versus the World: A New Label Attack Approach in Federated Environments Based on Bayesian Neural Networks - Barros, Pedro H.; Murai, Fabricio; Ramos, Heitor S. (Anais da Brazilian Conference on Intelligent Systems (BRACIS); 2023: Anais da XII Brazilian Conference on Intelligent Systems, 2023)
Federated Learning (FL) is a decentralized machine learning approach developed to ensure that training data remains on personal devices, preserving data privacy. However, the distributed nature of FL environments makes defense against malicious attacks a challenging task. This work proposes a new attack approach to poisoning labels using Bayesian neural networks in federated environments. The hypothesis is that a label poisoning attack model trained with the marginal likelihood loss can generate a less complex poisoned model, making it difficult to detect attacks. We present experimental results demonstrating the proposed approach’s effectiveness in generating poisoned models in federated environments. Additionally, we analyze the performance of various defense mechanisms against different attack proposals, evaluating accuracy, precision, recall, and F1-score. The results show that our proposed attack mechanism is harder to defend when we adopt existing defense mechanisms against label poisoning attacks in FL, showing a difference of 18.48% for accuracy compared to the approach without malicious clients.